Illustrated guide to the echinoid (Echinodermata: Echinoidea) fauna of South Africa - Filander, Zoleka; Griffiths, Charles (Zootaxa, 2017)
The sea-urchins (class Echinoidea) of South Africa have received little taxonomic attention since the last comprehensive regional monographic guide, which was published in 1976 and is thus now severely outdated. That account was also poorly illustrated, making it difficult to use. Recent work by the authors has also added some 19 additional species to the known fauna, which now stands at 70 species. The aims of this study are thus to revise and update the South African echinoid fauna list, and to present a new, easy to use and fully-illustrated guide to all known regional species. The analysis is based mainly on examination of samples from the Iziko South African Museum collections, although additional records from other museum collections, the published literature, photographic images submitted to the EchinoMap Virtual Museum Database and any other reliable records are also included. A short account of each species is given, including relevant synonymy and literature, and brief notes on identification, size, and global distribution. Photographs that best represent the diagnostic features of each species and a map showing its known records within the region accompany each species account. A binary key to species is also provided.